Chiwit thi thuk lamoet ruang lao kathoei thom di ying rak ying chai rak chai lae kotmai sitthi manutsayachon rawang prathet = Violated lives : narratives from LGBTIQs and international human rights law (Mūnnithi Thīranāt Kānčhanaʻaksō̜n, 2011)
Narratives from homosexuals, gays, and lesbians in Thailand and international human rights law.